Implementation Of Bcrypt Algorithm for SIPAPEDA Website Security at BAPPEDA Office, Buton Regency with One Time Password Method - Jabal Nur (JEAT : Journal of Electrical Automation Technology, 2023)
The Office of the Regional Development Planning Agency (BAPPEDA) of Buton Regency has a website, namely the Regional Development Design Data Processing Information System (SIPAPEDA) where the SIPAPEDA Website is used to input data as well as an information system from each office in Buton Regency. With the large number of users of the Website, the security on the Website must be improved. Based on these problems, the security of the SIPAPEDA website is improved by using the Bcrypt algorithm and using One Time Password (OTP) as verification at login. With the aim of securing the Sipapeda Website of Buton Regency using the Bcrypt Algorithm with the One Time Password (OTP) Authentication Method. In this study using data collection methods, namely observations, interviews and literature and data analysis that refers to the types of data and data sources. This study resulted in the Sipapeda website being able to increase its security using the Bcrypt algorithm, as well as security in the login process requiring OnTime Password verification.